Combined gene therapy of endostatin and interleukin 12 with polyvinylpyrrolidone induces a potent antitumor effect on hepatoma - Li, Pei-Yuan (World J Gastroenterol, 2004)
AIM: To study the antitumor effect of combined gene therapy of endostatin and interleukin 12 (IL-12) with polyvinylpyrrolidone (PVP) on mouse transplanted hepatoma. METHODS: Mouse endostatin eukaryotic plasmid (pSecES) with a mouse Igκ signal sequence inside and mouse IL-12 eukaryotic plasmid (pmIL-12) were transfected into BHK-21 cells respectively. Endostatin and IL-12 were assayed by ELISA from the supernant and used to culture endothelial cells and spleen lymphocytes individually. Proliferation of the latter was evaluated by MTT. H22 cells were inoculated into the leg muscle of mouse, which was injected intratumorally with pSecES/PVP, pmIL-12/PVP or pSecES + pmIL-12/PVP repeatedly. Tumor weight, serum endostatin and serum IL-12 were assayed. Tumor infiltrating lymphocytes, tumor microvessel density and apoptosis of tumor cells were also displayed by HE staining, CD31 staining and TUNEL. RESULTS: Endostatin and IL-12 were secreted after transfection, which could inhibit the proliferation of endothelial cells or promote the proliferation of spleen lymphocytes. Tumor growth was highly inhibited by 91.8% after injection of pSecES + pmIL-12/PVP accompanied by higher serum endostatin and IL-12, more infiltrating lymphocytes, fewer tumor vessels and more apoptosis cells compared with injection of pSecES/PVP, pmIL-12/PVP or vector/PVP. CONCLUSION: Mouse endostatin gene and IL-12 gene can be expressed after intratumoral injection with PVP. Angiogenesis of hepatoma can be inhibited synergisticly, lymphocytes can be activated to infiltrate, and tumor cells are induced to apoptosis. Hepatoma can be highly inhibited or eradiated.